2018
DOI: 10.1371/journal.pone.0198338
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior and testis morphology in the BACHD rat model

Abstract: BackgroundHuntington disease (HD) is an autosomal dominant neurodegenerative disorder caused by a mutation in the huntingtin (HTT) gene, which results in brain neurodegeneration and peripheral pathology affecting different organs including testis. Patients with HD suffer from motor and cognitive impairment, and multiple psychiatric symptoms. Among behavioral abnormalities in HD, sexual disturbances have often been reported, but scarcely investigated in animal models. The BACHD rat model of HD carries the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…To further explore the cells targeted by stress-induced spermatogenesis impairment, cells were counted within the spermatogenic epithelium (including Sertoli cells, spermatogonia, spermatocytes, and spermatids). The different types of cells within the spermatogenic epithelium are marked in Supplementary Figure S1A, and refer to the description presented in a previous study [15], and the spermatogenic epithelium of SD rats in different groups is shown in Supplementary Figure S1B. As shown in Figure 3A,B, the total number of cells within the spermatogenic epithelium decreased significantly in the uCMS group as compared to the control group (156.75 ± 40.44 versus 239.50 ± 23.81, p = 0.007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the cells targeted by stress-induced spermatogenesis impairment, cells were counted within the spermatogenic epithelium (including Sertoli cells, spermatogonia, spermatocytes, and spermatids). The different types of cells within the spermatogenic epithelium are marked in Supplementary Figure S1A, and refer to the description presented in a previous study [15], and the spermatogenic epithelium of SD rats in different groups is shown in Supplementary Figure S1B. As shown in Figure 3A,B, the total number of cells within the spermatogenic epithelium decreased significantly in the uCMS group as compared to the control group (156.75 ± 40.44 versus 239.50 ± 23.81, p = 0.007).…”
Section: Resultsmentioning
confidence: 99%
“…A Leica optical microscope (Leica Microsystems, Wetzlar, Germany) was used to assess histology and morphometry. To count the number of different testicular cells in situ, three randomly selected tubules in one hematoxylin-stained section of each animal were analyzed according to a previously described procedure [15]. Briefly, the number of Sertoli cells (located in the testicular basement membrane side with clearly identifiable nucleoli) and germ cells at different stages of maturation that included spermatogonia (located in the testicular basement membrane side with deeply stained nuclei), spermatocytes (larger size and deeply stained nuclei), and spermatids (smaller size and lightly stained nuclei) within the seminiferous tubules were manually counted in 10 animals per group.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we argue that this approach could be applied for more precise determination of specific mechanisms involved in abnormal or disturbed sexual behavior in rats that are translationally related to human health disorders. In particular, translational research in rodent models of sexual behavior has provided important insights into the pathomechanisms and pharmacotherapy of clinical conditions that are described in the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM 5) and in the International Statistical Classification of Diseases and Related Health Problems 10th revision (ICD-10), including premature ejaculation, paraphilias, mood and anxiety disorders as well as neurological and metabolic diseases (McVary et al, 1997;Grønli et al, 2005;Giuliano and Clément, 2006;Hawley et al, 2013;Pfaus et al, 2013;Kang et al, 2014;Olayo-Lortia et al, 2014;Sanna et al, 2014;Faulkner et al, 2015;Babaei-Balderlou and Khazali, 2016;Oosting et al, 2016;Ramírez-Rodríguez et al, 2017;Hernández and Fernández-Guasti, 2018;Novati et al, 2018). In this light, we propose that in various rodent models of human disease states, sexual motivation and performance may be differently affected, which is reflected in distinct changes of specific components of male rat sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: ACTH, adrenocorticotropic hormone; CRH, corticotropin-releasing hormone; EF, ejaculation frequency; HPG, hypothalamic-pituitary-gonadal axis; III, inter-intromission interval; PDE5, phosphodiesterase 5; PVs, precontact vocalizations in the 50-kHz band; SSRI, selective serotonin reuptake inhibitor. References in the table: [1] (Pfaus and Phillips, 1991, Van Furth et al, 1994, Barr et al, 1999; [2] (Bialy et al, 2000); [3] (Pfaus et al, 2013); [4] (Fiorino and Phillips, 1999); [5] (Novati et al, 2018); [6] (Barrot et al, 2005, Miwa et al, 2011; [7] (Pfaus and Phillips, 1991); [8] (Faulkner et al, 2015); [9] (Babaei-Balderlou and Khazali, 2016); [10] (Bialy et al, 2014); [11] (Sadeghzadeh et al, 2018); [12] (McVary et al, 1997); [13] (Hawley et al, 2013, Sanna et al, 2014; [14] (Ramírez-Rodríguez et al, 2017, Hernández andFernández-Guasti, 2018); [15] (Coolen et al, 1997, Pattij et al, 2005a, Clément et al, 2007, Kang et al, 2013, Olayo-Lortia et al, 2014; [16] (Grønli et al, 2005); [17] (de Jong et al, 2005, Hueletl-Soto et al, 2012; [18] (Coolen et al, 1997, Beck and; [19] (Harris and Sachs, 1975, Valcourt and Sachs, 1979, Novati et al...…”
Section: Intromission Ratiomentioning
confidence: 99%
“…Before sexual behaviour evaluations, all adult male mice were sexually experienced with oestrous female (1:1 ratio). Sexually mature female mice ( n = 16) were induced to be oestrous phase by subcutaneous injection with β‐estradiol‐3‐benzoate (10 µg/mouse; Sigma‐Aldrich), 48 hr before coupling then they were injected with progesterone (500 µg/mouse; Sigma‐Aldrich) (Novati et al., 2018). This test was conducted under dim light.…”
Section: Methodsmentioning
confidence: 99%